Functional analysis of the cyclophilin PpiB role in bacterial cell division. (28th July 2017) - Skagia, Aggeliki; Zografou, Chrysoula; Venieraki, Anastasia; Fasseas, Costas; Katinakis, Panagiotis; Dimou, Maria
Abstract : Escherichia coli PpiB is a peptidyl‐prolyl cis/trans isomerase (PPIase, EC: 5.2.1.8) with chaperone activity. Here, we show that the Δ ppiB deletion strain and the PpiB over‐expression wild‐type strain are both characterized by defects in cell division involving milder or severe cell filamentation, respectively. Using various PpiB mutants, we show that the PPIase activity of PpiB is necessary for the observed cell filamentation, whereas other structural features apart from the active site are also important for this phenotype. Early divisome components zipA and ftsZ showed decreased expression in Δ ppiB cells, whereas the corresponding proteins partially suppressed the division phenotype of Δ ppiB cells as well. Although PpiB itself has no obvious specific affinity for the septal ring as a GFP translational fusion showed a diffuse cytoplasmic localization, it interacts with FtsZ employing the C‐terminal FtsZ domain, decreases its GTPase activity and when over‐expressed shows an inhibitory effect on the proper FtsZ localization at future division sites. Furthermore, additional putative PpiB prey proteins are able to partially restore the Δ ppiB phenotype indicating that PpiB is able to control bacterial cell division by probably modulating the function of various other proteins which are indirectly associated with the process. Abstract : Alterations in the cytoplasmic cyclophilin PpiB levels negatively modulate bacterial cell division in a way that employs its prolyl isomerase activity as well as other structural features apart from the active site. PpiB is able to interact with the divisome component FtsZ and delocalize it from future division sites. Furthermore, PpiB seems to modulate the function of additional proteins not previously related to cell division.